The reflective practice as a tool for making tacit knowledge explicit. Issue 4 (4th July 2021) - Ravanal Moreno, Eduardo; Cabello, Valeria M.; López-Cortés, Francisco; Amórtegui Cedeño, Elias
ABSTRACT: Reflective practice is an essential professional development tool that allows teachers to provide meaning to experiences teaching practice. Reflecting on teaching is also an opportunity to identify relevant situations for stimulating teachers' thinking and meta-analysis to broaden the understanding of their schemas and their explicit and tacit knowledge involved in the teaching practices they promote. Few studies discuss reflective practice linking tacit and explicit teaching knowledge. In this framework, a case study was designed based on an in-service biology teacher's teaching practice. The teacher observed one of his biology classes and identified areas of concern. He subsequently participated in two semi-structured interviews to reflect on the difficulties he recalled in his practice. A qualitative analysis was carried out linking the observation with the teacher's ideas about his teaching regarding action-belief-reflection. The trilogy allowed identifying (a.) temporality as a subjective variable in reflection determines the teacher's internalized position about a teaching action, (b.) the teacher transformed tacit knowledge into explicit knowledge through two forms of reflection: the formulation of questions and the explanations in the classroom. We discuss the role of reflective practice as a plausible alternative to achieve teacher awareness about the guiding rules of a pedagogical action.